Predictors and long‐term outcome of super‐responders to cardiac resynchronization therapy. Issue 5 (14th March 2017) - Ghani, Abdul; Delnoy, Peter Paul H.M.; Adiyaman, Ahmet; Ottervanger, Jan Paul; Ramdat Misier, Anand R.; Smit, Jaap Jan J.; Elvan, Arif
Abstract : Background: The level of improvement in left ventricular ejection fraction (LVEF) in super‐responders to cardiac resynchronization therapy (CRT) is exceptional. However, the long‐term prognosis remains unknown in a large population. Hypothesis: Whether super‐responders haven good long‐term outcomes. Methods: We registered 347 patients with primary CRT‐D indication. Super‐response was defined by LVEF >50% at follow‐up echocardiogram. Best‐subset regression analysis identified predictors of super‐response. Endpoints were major adverse cardiac events (MACE; eg, all‐cause mortality or heart failure hospitalization, cardiac death, and appropriate ICD therapy). Results: Fifty‐six (16%) patients with LVEF >50% were classified as super‐responders. Female sex (OR: 3.06, 95% CI: 1.54‐6.05), nonischemic etiology (OR: 2.70, 95% CI: 1.29‐5.68), higher LVEF at baseline (OR: 1.07, 95% CI: 1.02‐1.13), and wider QRS duration (OR: 1.17, 95% CI: 1.04‐1.32) were predictors of super‐response. Cumulative incidence of MACE at a median of 5.3 years was 18% in super‐responders, 22% in responders, and 51% in nonresponders ( P  < 0.001). None of super responders died from cardiac death, compared to 9% of responders and 25% of non‐responders ( P < 0.001). None of super‐responders experienced appropriate ICD therapy, compared with 10% of responders and 21% of non‐responders ( P  < 0.001). In super‐responders, the adjusted hazard ratio was 0.37 (95% CI: 0.19‐0.73) for MACE and 0.44 (95% CI: 0.20‐0.95) for total mortality, compared with non‐responders. Conclusions: Female sex, non‐ischemic etiology, higher baseline LVEF, and wider QRS duration were independently associated with super‐response. Super‐response was associated with persistent excellent prognosis regarding survival and appropriate ICD therapy during long‐term follow‐up.